PENGEMBANGAN MEDIA PEMBELAJARAN ILMU PENGETAHUAN ALAM BERBASIS SWISHMAX DI MIN 2 PALEMBANG - Dispi Riska; Muhamad Afandi; Mardiah Astuti (Al-Mudarris: Journal Of Education, 2019)
The purpose of this study was to determine the level of validity, practicality and effectiveness of the development of Swishmax-based Natural Sciences learning media in IVG MIN 2 Palembang. This research method uses Research and Development (R & D) methods. The research and development model used is the tressmer model with the stages of research: the preliminary stage (preparation and design), the formative evalution stage (self evaluation, expert review, one to one, small group, and field test). Data collection techniques using questionnaires and tests. Data analysis techniques use percentages. The results of this study include: (1) Development of Swishmax-based Natural Sciences learning media in Palembang IVG MIN 2 Class can be categorized as valid. This is indicated by the acquisition of media expert validation scores of 84.5, language experts 82, and material experts 90; (2) The practicality level of the application of the development of Swishmax-based Natural Sciences learning media in Palembang IVG MIN 2 Class is very practical. This can be seen from the acquisition of the average questionnaire score of 100 in the field test stage; (3) The effectiveness of the development of Swishmax-based Natural Sciences learning media in Palembang IVG MIN 2 Class is very effective. It is known that the level of mastery learning in classical students reaches 95% in the field test stage.